P345 Impact of aphthous colitis at diagnosis on Crohn's disease outcomes. (16th January 2018) - Delattre, C; Nion-Larmurier, I; Bourrier, A; Landman, C; Le Gall, G; Kirchgesner, J; Sokol, H; Beaugerie, L; Cosnes, J; Seksik, P
Abstract: Background: The natural history of intestinal lesions in Crohn's disease (CD) is not completely characterised. Extent of the lesions at diagnosis usually defines the reference extent of the disease, and therefore influences therapeutic choices. However, it seems that some lesions seen at diagnosis, especially aphthous ulcer, might regress during follow-up. This question has never been addressed, although it could impact therapeutic decisions. The aim of our study was to evaluate the outcomes of CD colonic aphthous ulcers seen at diagnosis. Methods: All the CD patients with at least a colitis at diagnosis represented exclusively by aphthous ulcers (AU) and followed-up since 2001 in our tertiary centre were included in the study. The outcomes of this group of patients (AU) were compared through a case control study, to two control groups: one without colonic lesion at diagnosis and one with more severe than aphthous ulcers colonic lesions at diagnosis. The patients from the AU group were matched 1 on 2 on sex, age, and extent of the lesions at diagnosis. A multivariate analysis was performed to determine factors associated with ileal resection in this study. Results: Seventy-five patients with colonic AU at diagnosis were included, with a median follow-up of 7.3 years (IQR 2.7–9.8). Forty-five patients had a second colonoscopy (at least 6 month after the index colonoscopy), from whom 32 patients were endoscopically stable or healed (71%) and 13 (29%) had more severe colonic lesions. Considering therapeutic requirement, these patients had similar outcomes than those with severe colitis, and their rate of ileal surgery was similar to those without colonic involvement. No patient with aphthous colitis needed colonic resection during the follow-up. In multivariate analysis, the independent factors associated with ileal resection were ileal involvement (OR:8.8; CI 95% [7.68–33.75]; p = 0.002) and the presence a severe colitis ((OR = 0.5 ; CI95% [0.32–0.79], p = 0.003). The risk of ileal surgery was not influenced by the presence of an aphthous colitis (OR: 0.63 ; CI 95%(0.37–1.1); p = 0.1) Conclusions: Our study points out that aphthous colitis at diagnosis can regress in most patients. Our results suggest that in these patients one might not take into account these colonic lesions when making therapeutic choices, especially when ileal resection is required.